Neutrino trident scattering at near detectors - Ballett, Peter; Hostert, Matheus; Pascoli, Silvia; Perez-Gonzalez, Yuber F. [UNESP]; Tabrizi, Zahra; Funchal, Renata Zukanovich (Springer, 2019)
Neutrino trident scattering is a rare Standard Model process where a charged-lepton pair is produced in neutrino-nucleus scattering. To date, only the dimuon final-state has been observed, with around 100 total events, while the other channels are as yet unexplored. In this work, we compute the trident production cross section by performing a complete four-body phase space calculation for different hadronic targets. This provides a correct estimate both of the coherent and the diffractive contributions to these cross sections, but also allows us to address certain inconsistencies in the literature related to the use of the Equivalent Photon Approximation in this context. We show that this approximation can give a reasonable estimate only for the production of dimuon final-states in coherent scattering, being inadmissible for all other cases considered. We provide estimates of the number and distribution of trident events at several current and future near detector facilities subjected to intense neutrino beams from accelerators: five liquid-argon detectors (SBND, BooNE, ICARUS, DUNE and STORM), the iron detector of T2K (INGRID) and three detectors made of composite material (MINOS, NOA and MINERA). We find that for many experiments, trident measurements are an attainable goal and a valuable addition to their near detector physics programme.
Keywords: Neutrino Physics; Precision QED